2016
DOI: 10.1016/j.coviro.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Flavivirus modulation of cellular metabolism

Abstract: Over the last decade, we have begun to appreciate how flaviviruses manipulate cellular metabolism to establish an optimal environment for their replication. These metabolic changes include the stimulation of glycolysis, in addition to lipid anabolic and catabolic pathways. These processes are thought to promote an energetically favorable state, in addition to modifying membrane lipid composition for viral replication and virion envelopment. Importantly, many of these processes can be pharmacologically inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 33 publications
0
49
0
1
Order By: Relevance
“…The interpretation of clinical and laboratory data for the characterization of the severity of dengue disease is rather complex; however, recent studies have pointed out the value of circulating lipids as potential biomarkers. Targeting this biomacromolecule has gained appeal for its prognostic value for dengue because both in vivo and in vitro studies have shown that the DENV modulates lipid metabolism to enable the virus to infect host cells . In this study, we have summarized the current knowledge on the prognostic value of lipid levels in patients with dengue, and we have evaluated how different variables influence this association through meta‐analysis and subgroup assessment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The interpretation of clinical and laboratory data for the characterization of the severity of dengue disease is rather complex; however, recent studies have pointed out the value of circulating lipids as potential biomarkers. Targeting this biomacromolecule has gained appeal for its prognostic value for dengue because both in vivo and in vitro studies have shown that the DENV modulates lipid metabolism to enable the virus to infect host cells . In this study, we have summarized the current knowledge on the prognostic value of lipid levels in patients with dengue, and we have evaluated how different variables influence this association through meta‐analysis and subgroup assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemically, it is known that infection by DENV alters some components associated with triglyceride metabolism. During the multiplication phase, NS3 protein from DENV increases the activity of FASN, a rate‐limiting enzyme in triglycerides biosynthesis, in human cells . Perera and collaborators have demonstrated that the activation of FASN occurs also in mosquito cells, showing that the triglycerides have an emerging role in shaping the membrane and protein environments during viral infections of vector .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent advances have revealed that positive-stranded RNA viruses, including the flaviviruses, rearrange host cell lipid metabolism and coopt for cellular lipids to com-plete their life cycle (5)(6)(7). Considering this dependence on lipid metabolism during flavivirus infection, pharmacological modification of the lipid metabolic pathways appears to be a proper strategy to impair flaviviral replication (7,8).…”
mentioning
confidence: 99%